COVID-19 Complicated by Concomitant Renal, Splenic, and Myocardial Infarction: Double Whammy - Mehdi Ghaderian Jahromi; Marzieh Sheibani Abdolusefi; Mohsen Neshati Pir Borj (Case Reports in Acute Medicine, 2021)
A 76-year-old man presented with shortness of breath, fever, and fatigue with confirmed COVID-19 by positive RT-PCR test for the SARS-COV-2. Abdominal and pelvis computed tomography with intravenous contrast was performed several days later given the patient’s severe abdominal pain which showed both renal and splenic infarcts despite the use of a proper thromboprophylaxis with subcutaneous heparin, and therefore, therapeutic anticoagulation was initiated. In the course of hospitalization, he developed acute kidney injury, uremic syndrome, and myocardial infarction as well. The patient was treated with fibrinolytic therapy and was eventually discharged on a direct oral anticoagulant.